A nationwide peer-assisted learning program in disaster medicine for medical students. (August 2020) - Ragazzoni, Luca; Conti, Andrea; Dell'Aringa, Marcelo; Caviglia, Marta; Maccapani, Fabio; Della Corte, Francesco
Abstract : Objectives: The Sendai Framework advocates the importance of training in disaster medicine as a way to improve health system resilience. In Italy, despite the official recognition of disaster medicine as a mandatory discipline in the standard curriculum, most students are never exposed to its basic concepts. DisasterSISM is a nationwide educational program in disaster medicine developed in 2008. Given the scarcity of experienced instructors, in 2013, the course adopted a peer-assisted learning (PAL) approach to correct the omission identified in the national curriculum. The new approach involved a training of trainers (ToT) and a basic course organized and delivered by certified student teachers. Methods: The authors gathered and analyzed data from demographic questionnaires, pretest and posttests, and satisfaction questionnaires. Results: From 2013 to 2018, 42 medical students attended the ToT becoming student teachers. From 2014 to 2018, 2316 medical students attended the basic course delivered by the student teachers across Italy. Thirty-six out of 41 medical schools were reached. Participation in the program improved students' knowledge in disaster medicine. Participants were satisfied with both the course structure and its PAL approach and considered disaster medicine to be highly relevant for their future professional career. Conclusions: By presenting this nationwide program and its outcomes, the authors hope to strengthen the case for including disaster medicine education in the standard medical curriculum. Because the course relies on medical students and PAL, the authors trust that it could be adapted to other countries worldwide.